A highlight from the LUPUS 2014 meeting: eight great ideas. Issue 1 (30th June 2015) - Buyon, Jill P; Cohen, Phillip; Merrill, Joan T; Gilkeson, Gary; Kaplan, Mariana; James, Judith; McCune, W Joseph; Bernatsky, Sasha; Elkon, Keith
Abstract : This review describes eight 'great ideas' regarding bench-to-bedside considerations in systemic lupus erythematosus (SLE) presented at the second international LUPUS meeting in Quebec, September 2014. The topics included: correcting the impaired clearance of apoptotic fragments; optimisation of clinical trial design: the PERFECT (Pre Evaluation Reducing Frighteningly Elevated Coverable Targets) study; lipidomics and metabolomics in SLE; importance of the inflammasome; identification and treatment of asymptomatic autoimmunity: prevention of SLE; combining low doses of hydroxychloroquine and quinacrine for long-term maintenance therapy of SLE; reducing emergency room visits and the critical relevance of the autoantigen.